Petersburg Flood of 1824: Eschatological Narratives and Their Visual Representation - Egorova, Kseniya B. (Actual Problems of Theory and History of Art, 2022)
The article deals with the formation of eschatological narratives around the St. Petersburg flood of 1824. The literary and visual material shows how eschatological plots were created in Russian culture under the influence of the European tradition. A hypothesis is put forward that the visual history of the St. Petersburg flood can only be considered in connection with and in the context of the European history of painting, in relation to well-known compositions and plots. The eschatological narrative about the death of Peter’s creation, the new Babylon, from the Neva waters should be considered not in the gospel tradition of the coming Apocalypse, but through the prism of Byron’s story about the last Assyrian king Sardanapal, which, obviously, influenced the idea of the 3rd part of Mickiewicz’s Dziads, who first proposed the apocalyptic interpretation of regular St. Petersburg natural disasters.The reported study was funded by the Russian Science Foundation, project number 21-78-10052.
Keywords: Russian literature; eschatology; depiction of floods; the Flood; the Apocalypse; Mickiewicz; The Bronze Horseman; graphics; Academy of Arts